If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -12 = 3x + 0 Reorder the terms: -12 + 9x = 3x + 0 Reorder the terms: -12 + 9x = 0 + 3x Remove the zero: -12 + 9x = 3x Solving -12 + 9x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -12 + 9x + -3x = 3x + -3x Combine like terms: 9x + -3x = 6x -12 + 6x = 3x + -3x Combine like terms: 3x + -3x = 0 -12 + 6x = 0 Add '12' to each side of the equation. -12 + 12 + 6x = 0 + 12 Combine like terms: -12 + 12 = 0 0 + 6x = 0 + 12 6x = 0 + 12 Combine like terms: 0 + 12 = 12 6x = 12 Divide each side by '6'. x = 2 Simplifying x = 2
| -5+5=25 | | 2x1/10= | | Y-(-5)=-2/6(x-4) | | X^2+13x=86 | | -9q=108 | | 546=p*.05*2 | | 3(2x+5)+2(2+1)=37 | | 59+35+11=180 | | 2k-7+2=7 | | 7-3x=-3x-8 | | x+y+z=-16 | | 63+36+13=180 | | 5bx+2=2a | | 3i+8=8+3i | | 63.05=p*.0325*2 | | -5y-15x=20 | | 7+5v=12 | | 784=(20-2x)(40-2x) | | 5x-7-2x=-19 | | -9-2-16=-23 | | 57.75=550*r*3 | | f(x)=-2x^2+3x+9 | | 8c-12x=36 | | 694=6k | | 3(-2x+2)+10x=3(x+1)+x+3 | | 3.6x=-9 | | (5x^2y-2xy^2+y^3)-(4x^2y-2xy^2)= | | 1/7•300=x | | z*3.2+7.42=9.81 | | 54=150*.06*t | | 3mx-2n= | | 4/5y=4/10 |